Postwar Urban Redevelopment and the Politics of Exclusion: The Case of San Francisco's Chinatown. (February 2019) - Li, Chuo
This article examines the landscape changes of San Francisco's Chinatown resulting from urban redevelopment after World War II. It describes the contested process of community development and documents the intricacies of Chinatown's spatial struggles. Socially constructed as a space of "otherness, " San Francisco's Chinatown illustrates the ways in which urban redevelopment process interacted with the social and cultural tensions of a plural and liberal urban society. It also reveals how the existing categories of ethnicity and cultural identity have been renegotiated over time.